Principles of Epigenetic Homeostasis Shared Between Flowering Plants and Mammals. Issue 10 (October 2020) - Williams, Ben P.; Gehring, Mary
Abstract : In diverse eukaryotes, epigenetic information such as DNA methylation is stably propagated over many cell divisions and generations, and can remain the same over thousands or millions of years. However, this stability is the product of dynamic processes that add and remove DNA methylation by specialized enzymatic pathways. The activities of these dynamic pathways must therefore be finely orchestrated in order to ensure that the DNA methylation landscape is maintained with high fidelity – a concept we term epigenetic homeostasis. In this review, we summarize recent insights into epigenetic homeostasis mechanisms in flowering plants and mammals, highlighting analogous mechanisms that have independently evolved to achieve the same goal of stabilizing the epigenetic landscape. Highlights: DNA methylation landscapes are consistently maintained by dynamic processes over evolutionary timescales. Both animals and plants possess robust positive feedback mechanisms that reinforce methylated DNA with high fidelity. Plants have evolved at least three epigenetic homeostasis mechanisms that balance robust methylation pathways, including the DNA methylation-dependent expression of the demethylase ROS1 and the DNA methylation-dependent splicing of the histone demethylase IBM1 . Analogous mechanisms have likely evolved in mammals. Mutants of TET demethylases exhibit DNA hypomethylation, suggesting that the TET pathway operates as part of a feedback loop that ensures proper DNMT3 function.